A Study on Consumer Behaviour of Women with Special Reference to Durable Goods in Coimbatore City, Tamil Nadu - Saravanan, S. (Indian Journal of Marketing, 2010)
There are many underlying influences both internal and external from the social environment. The combination of these inputs and internal factors can never be complex indeed. Yet, the tools of market research can assess motivation and behaviour with considerable accuracy. Perfect prediction of behaviour is never possible, but properly designed research efforts can significantly lower the risks of the types of product failure. While the consumer cannot knowingly be induced to act in a way contradictory to his or her own goals, motivation and behaviour can be influenced by outside sources. This influence is understood through research.